Dinamika Kontrol Diri dan Boredom Proneness dalam Membentuk Perilaku Phubbing Generasi Z di Kota Karawang - Sheila Handayani Supriatna; Lania Muharsih; Mohammad Iqbal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology, particularly the use of smartphones among Generation Z, has given rise to the phenomenon of phubbing, which is the behavior of ignoring the person being talked to by diverting attention to a mobile device in social interaction situations. This study aims to examine the influence of self-control and boredom proneness on phubbing behavior among Generation Z in Karawang City. The method used was quantitative with a causal associative design, involving 204 participants selected through a quota sampling technique. Data collection used three validated instruments, namely the Phubbing Scale (PS), Brief Self-Control Scale (BSCS), and Short Boredom Proneness Scale (SBPS). Data analysis was conducted using multiple linear regression tests. The results showed that self-control and boredom proneness simultaneously had a significant effect on phubbing behavior, with a significance value of 0.000 < 0.05 and a contribution of 7.8%. Weak self-control and boredom drive someone to reflexively reach for a smartphone, even when they are with other people. This study concluded that self-control and boredom proneness significantly influence phubbing behavior among Generation Z in Karawang City.